2006
DOI: 10.1063/1.2360182
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous cross field electron transport in a Hall effect thruster

Abstract: The origin of anomalous electron transport across the magnetic field in the channel of a Hall effect thruster has been the subject of controversy, and the relative importance of electron-wall collisions and plasma turbulence on anomalous transport is not clear. From comparisons between Fabry-Pérot measurements and hybrid model calculations of the ion velocity profile in a 5kW Hall effect thruster, we deduce that one and the same mechanism is responsible for anomalous electron transport inside and outside the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 14 publications
5
62
1
Order By: Relevance
“…This indicates that higher discharge voltage has a negative impact on the anomalous electron diffusion, as was observed in Ref. [5] where the anomalous coefficient increased as the discharge voltage decreased below 400 V.…”
Section: Approximation Of Radial Magnetic Field Distribution With Givsupporting
confidence: 52%
See 3 more Smart Citations
“…This indicates that higher discharge voltage has a negative impact on the anomalous electron diffusion, as was observed in Ref. [5] where the anomalous coefficient increased as the discharge voltage decreased below 400 V.…”
Section: Approximation Of Radial Magnetic Field Distribution With Givsupporting
confidence: 52%
“…Thus, it can be seen that higher electron anomalous diffusion is required for the thruster to sustain discharge in the case of lower anode mass flow rate operation, which, in turn, indicates that if the anomalous electron diffusion is insufficient, , because the anomalous diffusion should be approximately doubled from the experimental results [5,18], 50 and 80 are taken as the lower and upper bounds, respectively. The selected ranges of the anomalous coefficients will be fixed in this paper and the investigation of varying the ranges is left for future work.…”
Section: Numerical Exploration For Ranges Of the Anomalous Coefficientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various theories have been proposed to explain the anomalous electron transport. Some [2,3] deemed that the anomalous electron transport is caused by plasma turbulence, which is known to produce a cross field electron mobility that varies like 1 B (described with Bohm-type anomalous conductivity). However, experimental results showed that, if the magnetic field intensity increases towards the outlet, the Bohm conductivity is restrained [4].…”
Section: Introductionmentioning
confidence: 99%